Compactness of Protein Folds Alters Disulfide‐Bond Reducibility by Three Orders of Magnitude: A Comprehensive Kinetic Case Study on the Reduction of Differently Sized Tryptophan Cage Model Proteins. (18th November 2019) - Horváth, Dániel; Taricska, Nóra; Keszei, Ernő; Stráner, Pál; Farkas, Viktor; Tóth, Gábor K.; Perczel, András
Abstract: A new approach to monitor disulfide‐bond reduction in the vicinity of aromatic cluster(s) has been derived by using the near‐UV range ( λ =266–293 nm) of electronic circular dichroism (ECD) spectra. By combining the results from NMR and ECD spectroscopy, the 3D fold characteristics and associated reduction rate constants ( k ) of E19_SS, which is a highly thermostable, disulfide‐bond reinforced 39‐amino acid long exenatide mimetic, and its N‐terminally truncated derivatives have been determined under different experimental conditions. Single disulfide bond reduction of the E19_SS model (with an 18‐fold excess of tris(2‐carboxyethyl)phosphine, pH 7, 37 °C) takes hours, which is 20–30 times longer than that expected, and thus, would not reach completion by applying commonly used reduction protocols. It is found that structural, steric, and electrostatic factors influence the reduction rate, resulting in orders of magnitude differences in reduction half‐lives (900> t 1/2 >1 min) even for structurally similar, well‐folded derivatives of a small model protein. Abstract : Breaking bonds : Structural, steric, and electrostatic factors influence the disulfide bond reduction rate, which results in three orders of magnitude differences in reduction half‐lives for N‐proximal truncated disulfide bond cyclized exenatide derivates. If the disulfide bond is near an aromatic cluster, near‐UV electronic circular dichroism spectral changes can be used to monitor reduction.